Solitary waves for a fractional Klein–Gordon–Maxwell equations - Xin Zhang (Electronic Journal of Qualitative Theory of Differential Equations, 2021)
We investigate existence of solutions for a fractional Klein–Gordon coupled with Maxwell's equation. On the basis of overcoming the lack of compactness, we obtain that there is a radially symmetric solution for the critical system by means of variational methods.